The Causality Analysis of the Effect of Oil and Natural Gas Prices on Ukraine Stock Index - Suleymanli, Javid Elkhan; Rahimli, Etimad Munasib; Akbulaev, Nurkhodzha Nazirkhodzha (International Journal of Energy Economics and Policy, 2020)
Since petroleum and natural gas are the main energy source, it is important for all countries in the world. Oil and natural gas reserves in the world are not evenly distributed; some countries are important oil and natural gas exporters while the others import these energy sources. For this reason, both exporting and importing countries have to pay close attention to oil and gas prices. For Ukraine, which imports more than 90% of its oil and natural gas needs, it makes the investigation of macroeconomic effects of the change in oil and natural gas prices extremely vital. There are many domestic and foreign studies investigating the interaction between oil and gas prices and both macro and micro economic variables in Ukraine. In this study, the effects of changes in oil and natural gas prices on the returns of the PFTS national index of the Ukrainian Stock Exchange were investigated. The study includes monthly data for January 2008 - September 2019 period. The Johansen cointegration test was conducted to determine whether the energy prices and PFTS index are cointegrated in the long run. According to the causality test, it was found that the change in oil price by 1 dollar and the change in natural gas price by 1 dollar cause the change in RFTS by 0.56 and by 0.31, respectively. Keywords: Ukraine, stock exchange, index, return, oil, natural gas, price. JEL Classifications: F30, F65, G12, G15 DOI: https://doi.org/10.32479/ijeep.9156